Financial Technology as Payment Methods in the Digital Era - I Budiarti; F Hibatulloh; M Salman (International Journal of Research and Applied Technology (INJURATECH), 2021)
FinTech is defined as technological innovation in financial services that can produce business models, applications, processes, or products with material effects related to financial services provision. This study aims to analyze the impact of developing a digital payment system and prevent inflation due to a large amount of cash in circulation. The method used in this study is qualitative. Fintech technology is very beneficial for the community, especially in industrial revolution 4.0, where this digital payment system has advantages and disadvantages. The advantages are efficiency and safety, while the disadvantages are higher interest costs. This digital payment system can minimize inflation due to the large amount of money circulating in society.